Ornamental aquarium organisms trade in Bangladesh - Noor-; ABM Mohsin (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2022)
The study was conducted in Dhaka, Bangladesh, and was carried out for twelve (12) months from March 2018 to February 2019 with a view to represent the trading diagram of ornamental fish in Bangladesh. During the current study 270 varieties (230 freshwater, 36 marine, and 4 brackish water) belong to 149 species (109 freshwater 73%, 36 marines 24%, and 4 brackish water 3%) of 38 families under 10 orders and 6 crossbreeds' varieties were recorded. Considering the number of species maximum 83 (55.70%) was found under the order Perciformes followed by Cypriniformes 24 (16.10%), Characiformes 18 (12.08%), Siluriformes 11 (7.38%), Osteoglossiformes 05 (3.35%), Atheriniformes 03 (2.01%), Lepisosteiformes 02 (1.34%), Polypteriformes 01 (0.6%), Myliobatiformes 01 (0.67%) and Cyprinodontiformes 01 (0.67%). The top five popular species were guppy (13.16%) followed by goldfish (12.39%), molly (8.54%), angelfish (6.23%), platy (5.93%). Most of the ornamental fish species were imported by importers from Thailand, Singapore, Indonesia, India, Malaysia, and Japan on the basis of demand. Then the imported shipment of aquarium fish and fish products was distributed among Dhaka Katabon fish shops, wholesalers, and retailers, according to their given order. After that, these were again distributed locally, to aquarium shops, breeders, ornamental fish farms all over the country. General customers and hobbyists purchase ornamental fish and aquarium products from local aquarium shops and businesses. The increasing tendency of the number of fish species was 5.96 times in the last 15 years and 3.31 times in the last 10 years. Local farms and aquarists' breeders bred 76 varieties under 23 species due to its high demand and profitability. Pricing varied on varieties, species, size, and breeding status (local or abroad), availability and ranged from BDT 40.00-80,000.00 per pair. Considering the findings, aquarium fisheries is highly profitable at present and it will be a potential sector in Bangladesh.